Effectiveness of eye movement modeling examples in problem solving: The role of verbal ambiguity and prior knowledge. (December 2018) - van Marlen, Tim; van Wermeskerken, Margot; Jarodzka, Halszka; van Gog, Tamara
Abstract: Eye movement modeling examples (EMME) are video modeling examples with the model's eye movements superimposed. Thus far, EMME on problem-solving tasks seem to be effective for guiding students' attention, but this does not translate into higher learning outcomes. We therefore investigated the role of ambiguity of the verbal explanation and prior knowledge in the effectiveness of EMME on geometry problems. In Experiment 1, 57 university students observed EMME or regular video modeling examples (ME) with ambiguous verbal explanations. Eye-tracking data revealed that –as in prior research with unambiguous explanations- EMME successfully guided students' attention but did not improve test performance, possibly due to students' high prior knowledge. Therefore, Experiment 2, was conducted with 108 secondary education students who had less prior knowledge, using a 2 (EMME/ME) x 2 (ambiguous/unambiguous explanations) between-subjects design. Verbal ambiguity did not affect learning, but students in the EMME conditions outperformed those in the ME conditions. Highlights: Eye movement modeling examples (EMME) guide attention via the model's eye movements. Two experiments examined EMME's effectiveness for learning to solve problems. University and secondary students learned geometry problem solving with/without EMME. EMME improved secondary but not university students learning. EMME effectiveness seems to depend on the level of prior knowledge of the learner.